The hunger in me / Suzana Ab. Rahim - Ab. Rahim, Suzana (Academy of Language Studies, 2022)
Oh honey! it's juz 4.20 and i'm hungry shall we blame it on the day that is rainy or is it the growling tummy uttering senseless help me! to the mind that's supposed to be brainy.. alas...for whatever is worth the penny will u kindly bring me food, honey?